THE IDEO-ARTISTIC SELF-IMAGE OF LOVE LYRICS A. A. AKHMATOVA - Navruzova Elena Pavlovna (Journals Park Publishing, 2022)
In this article, we have examined the love lyrics of A. A. Akhmatova. The article analyzes one of the poems by A. Akhmatova.
Keywords: Anna Akhmatova,; creator; woman